Application of optimization techniques to structural analyses: Truss example - Toklu, Yusuf Cengiz (My University, 2004)
Applications of continuously developing optimization techniques to design and analysis of structures have resulted in very elegant solutions for weight, shape and topology optimization of trusses, frames and other structures. In the algorithms used for this purpose, while the search for the best configuration is performed by the optimization technique chosen, the related structural analysis is carried on by "classical" methods, the most outstanding one being the finite element method. Now it is being shown that the structural analyses themselves can be performed by genetic algorithm, simulated annealing or the like. This new approach, being very practical and standing on very sound simple principles, also have enormous advantages over all other methods including finite element or boundary element methods and present itself as a very efficient structural analysis method, to say the least. The method is successfully applied to trusses with material and geometrical nonlinearities, until and exceeding the loss of stability, giving the deflected shape with very high accuracy. Although the method is applied to trusses in this analysis, it has been explained that it can be generalized for being applied to the analysis of more general types of stratures. Besides being an effective tool for structural analysis, the method can be extended to be used as a design tool in finding the optimum shapes taking into account nonlinear behavior.
Proceedings of the 2004 Structures Congress - Building on the Past: Securing the Future --
Keywords: Boundary element method; Deflection (structures); Finite element method; Genetic algorithms; Matrix algebra; Simulated annealing; Structural analysis; Structural frames; Trusses; Energy theorems; Geometrical nonlinearity; Nonlinear matrix equations; Structural optimization